Knowledge management framework collaborative project in the UAE Aviation Industry - Mohamed Alaffad Alhamodi, Ali Mohamed Khamis (2023)
Over the last decade, the aviation industry in the United Arab Emirates has seen intense competition. Within the aviation industry, there is a dearth of collaboration projects. This is attributed to the several collaboration projects established within the global aviation industry. The previous literature did not take into consideration the role of stakeholders’ trust in easing collaborative projects. The purpose of this research is to look into the role of knowledge management dimensions in collaborative projects. Besides that, this study also aims to determine the mediation role of stakeholder trust in the relationship between knowledge management dimensions and collaborative projects in the UAE aviation industry. Also, establishing a framework for knowledge management toward collaborative projects. A cross-sectional time horizon was used to collect the data from 373 employees with a response rate of 79.4% using a questionnaire as an instrument in the aviation sector of the United Arab Emirates. The obtained data was analyzed using PLS-SEM in order to develop structural equation modeling. The findings of this study revealed that two dimensions of knowledge management—stakeholders’ knowledge and community nodes of practice—were found to have a significant effect on collaborative projects. While nodes of internal practice and behaviors of practice were found to have no significant effect on the collaborative projects. In addition, stakeholder trust had no significant mediation role in the relationship between the knowledge management dimensions and the collaborative projects. This study established a framework for performing collaborative projects in the aviation industry. Thus, this study contributes to the knowledge of aviation management by identifying factors of an effective knowledge management system that would be applicable to the UAE aviation industry. This study adds to knowledge management theory by addressing the role of stakeholder trust in obtaining collaborative projects